Questions about the presence/absence of colour: From the cosmic reality of light through personal sensory quality to the aesthetic experience of colour - Lieber, Erzsébet (ARTCADIA, 2025)
Art has always sought to formulate physical and spiritual ideas, knowledge, and apparent paradoxes related to light and color in the language of forms and colors. In addition to or following their symbolic, representational, and expressive roles subordinate to the subject matter, color values have become equal image-forming forces. In the 20th century, partly as a result of scientific results, the focus shifted to the independent meanings of color and paint, or to color liberated from matter. Stimuli that allow us to see colors arise through physical processes, yet the colors themselves are the combined results of the operation of color perception – hardware of the nervous system, and software of the brain. Color is a quality dependent on the measurable wavelength and frequency of the light range of the electromagnetic field, as well as the energy level of its quanta, the photons, which we perceive physiologically with our vision. Visible color is a complex information package: one strand of it originates in the universe of physical or cosmic light, another in the deep tissue of material world, a third in the biological and chemical structure of the visual organ, a fourth in the brain and visual information processing capabilities of the seer, and in the sophistication of their mental and emotional apparatus. What information do colors carry in themselves and in their space-form-time relations? The study deals with such questions, touching on the most current issues of the relationship between color, theoretical physics, and contemporary art.